The Effect of Brand Image and Omni Channel Marketing on Customer Satisfaction and Customer Loyalty in Digital Saving Opening of Bank BRI - Natalina, Kristina; Wahyuni, Dr. Sri (UTSAHA: Journal of Entrepreneurship, 2022)
This research was conducted to determine descriptively and empirically the effect of brand image and omni channel marketing on customer satisfaction and customer loyalty in digital saving opening of Bank BRI. The population in this research is Bank BRI customers who have at least used a BRI Bank account for 5 years. Methods of data collection using the survey method. Data analysis used SPSS version 22 and SEM (Structural Equation Model) from the statistical package LISREL 8.7 to process and analyze the research data. The results of the descriptive test explained that the brand image and omni channel marketing provided were good based on customers satisfaction. Therefore, the customers were satisfied and tended to be loyal in digital saving opening of Bank BRI. The results of hypothesis testing indicate that: (1) brand image affects customer satisfaction positively and significantly; (2) omni channel marketing affects customer satisfaction positively and significantly; (3) brand image affects customer loyalty positively and significantly; (4) omni channel marketing affects customer loyalty positively and significantly; (5) customer satisfaction affects customer loyalty positively and significantly; (6) brand image and omni channel marketing affect customer loyalty through customer satisfaction as a mediating variable; and (7) Customer Satisfaction Has Positive Effect on Customer Loyalty